Short‐term forecasts of Monkeypox cases in multiple countries: keep calm and don't panic. Issue 1 (29th September 2022) - Mingione, Marco; Ciccozzi, Massimo; Falcone, Marco; Maruotti, Antonello
Abstract: We propose a parametric regression model for incidence indicators based on the use of the Richards' curve (a generalized logistic function) to analyse the current Monkeypox epidemic data for the most 10 affected countries worldwide. At present, results show that the outbreak is under control in most countries.